Oxygen-driven relaxation processes in pre-irradiated Ar cryocrystals - Savchenko, E.V.; Belov, A.G.; Gumenchuk, G.B.; Ponomaryov, A.N.; Bondybey, V.E. (Физика низких температур, 2006)
Relaxation processes in oxygen-containing Ar cryocrystals pre-irradiated by low-energy electrons
are studied with the focus on the role of diffusion controlled atom-atom recombination reaction
of oxygen in the relaxation cascades. The results of correlated in real time measurements of
thermally stimulated phenomena are presented. The experiments have been performed using activation
spectroscopy methods — thermally stimulated exoelectron emission and spectrally resolved
thermally stimulated luminescence. Solid evidence of the radiative mechanism of electron detrapping
triggering the relaxation cascades is obtained.